Education System in Bukhara Emirate - Gulamov Husanboy (Researchparks Publishing, 2022)
Ashtarkhanid rule, Mangit dynasty, transformation of Bukhara khanate into emirate, khanate and emirate educational systems, changes of power, influence of political situations on education, struggles for power.